The causal relationship between circulating metabolites and gestational hypertension, pre-eclampsia, eclampsia: A bidirectional two-sample Mendelian randomization study - Shi Guo; Yuting Su; Yajun Li; Cuiyuan Li; Lele Pan (Clinical and Experimental Hypertension)
Objective Gestational hypertension, pre-eclampsia, and eclampsia pose significant risks to maternal and fetal health, yet their underlying causes remain unclear. This study investigates the associations between 233 metabolites and these conditions.Methods We analyzed data from the Genome-Wide Association Studies (GWAS) database for gestational hypertension, pre-eclampsia, and eclampsia. The bidirectional two-sample MR analysis examined causal relationships using inverse variance weighting as the primary method, supplemented by MR-Egger, weighted median, simple mode, and weighted mode. Sensitivity analyses assessed robustness, heterogeneity, and horizontal pleiotropy.Results In the forward Mendelian randomization analysis, a reduction in citrate levels (OR = 0.906, 95% CI = 0.829–0.990, p = .029) is associated with an increased risk of gestational hypertension. The ratio of conjugated linoleic acid to total fatty acids (OR = 1.172, 95% CI = 1.026–1.339, p = .019) is associated with an increased risk of gestational hypertension. The ratio of conjugated linoleic acid to total fatty acids (OR = 1.288, 95% CI = 1.064–1.560, p = .009) is associated with an increased risk of preeclampsia and eclampsia. The phospholipids to total lipids ratio in large HDL (OR = 1.227, 95% CI = 1.120–1.344, p = 9.91 × 10^-6) is associated with an increased risk of preeclampsia and eclampsia. The total cholesterol to total lipids ratio in chylomicrons and extremely large VLDL (OR = 0.884, 95% CI = 0.789–0.990, p = .033) is associated with an increased risk of preeclampsia and eclampsia. In the reverse Mendelian randomization analysis, the occurrence of gestational hypertension is associated with a reduction in Cholesteryl esters to total lipids ratio in very large VLDL (OR = 0.987, 95% CI = 0.975–0.999, p = .044). The occurrence of preeclampsia and eclampsia is associated with a reduction in total choline levels (OR = 0.989, 95% CI = 0.979–0.998, p = .029), and with a reduction in total phosphoglycerides levels (OR = 0.988, 95% CI = 0.978–0.997, p = .012). Sensitivity analysis did not detect significant heterogeneity or pleiotropy.Conclusion This research elucidates the causal links between specific metabolites and gestational hypertension, pre-eclampsia, and eclampsia, potentially informing new clinical approaches for diagnosis and treatment.